2008
DOI: 10.1002/ajmg.a.32468
|View full text |Cite
|
Sign up to set email alerts
|

BMPR2 mutation in a patient with pulmonary arterial hypertension and suspected hereditary hemorrhagic telangiectasia

Abstract: Pulmonary arterial hypertension (PAH) and hereditary hemorrhagic telangiectasia (HHT) are distinct clinical entities caused by germline mutations in genes encoding members of the TGFbeta/BMP superfamily: BMPR2 in PAH and ACVRL1, ENG, or SMAD4 in HHT. When PAH and HHT occasionally co-exist within the same family, ACVRL1 mutations predominate. We report a 36-year-old woman initially diagnosed with PAH at age 24. At 35, following massive hemoptysis, multiple pulmonary arteriovenous malformations were discovered, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 29 publications
(51 reference statements)
1
35
0
Order By: Relevance
“…BMPs exert their effects via a heteromeric receptor complex, which consists of two types of serine-threonine kinase transmembrane receptors. BMPRII is the type 2 receptor of BMPs; mutations in BMPRII lead to the development of hereditary pulmonary hypertension, and its knockout results in early embryonic lethality [20,21]. BMPRII initiates intracellular signaling in response to the following specific ligands: BMP-2, BMP-4, BMP-6, BMP-7, growth and differentiation factor (GDF)-5, and GDF-6 [22].…”
Section: Introductionmentioning
confidence: 99%
“…BMPs exert their effects via a heteromeric receptor complex, which consists of two types of serine-threonine kinase transmembrane receptors. BMPRII is the type 2 receptor of BMPs; mutations in BMPRII lead to the development of hereditary pulmonary hypertension, and its knockout results in early embryonic lethality [20,21]. BMPRII initiates intracellular signaling in response to the following specific ligands: BMP-2, BMP-4, BMP-6, BMP-7, growth and differentiation factor (GDF)-5, and GDF-6 [22].…”
Section: Introductionmentioning
confidence: 99%
“…MADH4 encodes Smad-4, a downstream transcription factor of ALK1. The remaining cases of HHT attributed to an identified gene account for <1% of total cases and are caused by mutations in GDF2/BMP9, a TFG-β ligand, and BMPR2, a type 2 TGF-β receptor [1] [6] [10].…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary arterial hypertension (PAH) and HHT are autosomal dominant disorders of the vascular system caused by germline mutations in genes encoding members of the transforming growth factor (TGF)-beta superfamily, BMPR2 in the case of PAH and ALK1 or endoglin (ENG) in the case of HHT (13,14). While PAH and HHT are reported to be distinct clinical entities, and ALK1 mutations predominate in cases with coexisting PAH and HHT (15), Fujiwara et al (16) reported a high number of ALK1 mutations in pediatric PAH patients without HHT.…”
Section: Discussionmentioning
confidence: 99%
“…They proposed that ALK1 has as notable a role as BMPR2 in the etiology of PAH. On the other hand, Rigelsky et al (13) reported a rare case of BMPR2 mutation in a patient with HHT with multiple AVMs and PAH. They suggested that individuals with HHT alone who are negative for mutations in ALK1 and ENG should also be tested for mutations in BMPR2.…”
Section: Discussionmentioning
confidence: 99%